Optimizing Formative and Summative Assessment in Early Childhood Education: A Case Study of Sekolah Penggerak in Jambi City - Ratna Sari; Mastikawati; Fitriah; Azwir; Resti Puspa Reni; Amiroh; Lina Gurung (Journal of Early Childhood Development and Education, 2025)
Background of the Study:In the context of Indonesia’s Merdeka Curriculum, assessment plays a crucial role in supporting student-centered learning, particularly in early childhood education (ECE). The Sekolah Penggerak initiative aims to improve the quality of teaching and learning through the integration of formative and summative assessments. However, challenges persist in effectively implementing these assessments at the ground level, especially in PAUD (Early Childhood Education) settings. Aims and Scope of the Paper:This study aims to examine how formative and summative assessments are implemented in Sekolah Penggerak PAUD institutions in Jambi City, and to explore teacher perceptions, implementation challenges, and the effectiveness of these assessments in improving student learning outcomes. Methods:A qualitative descriptive approach was used, involving 21 early childhood educators from selected Sekolah Penggerak. Data were collected through structured questionnaires distributed via Google Forms and analyzed thematically using the Miles and Huberman framework. Results:The findings indicate that formative assessments are actively used during the learning process to provide immediate feedback that enhances student engagement and understanding. Summative assessments are used to evaluate overall competency achievement at the end of a learning period. However, teachers face significant challenges, including time limitations, administrative burdens, and insufficient technical support. Conclusion:The study highlights the need for ongoing professional development and context-specific assessment strategies to ensure the effective integration of formative and summative assessments in early childhood education. The results offer practical implications for policy-makers, school leaders, and educators seeking to improve assessment practices within the Merdeka Curriculum framework.